The importance of quality, satisfaction, trust and image in relation to rural tourism loyalty - Loureiro, S. M. C.; Miranda, F. J. M. (Journal of Travel and Tourism Marketing, 2008)
In the past decade, tourism firms have become aware of the great benefits of maintaining a solid base of loyal customers. Because rural tourism is a relatively new phenomenon in some countries, the main antecedent of tourism loyalty remains infrequently studied in rural lodgings. In this work, a structural equations model is explored, with PLS technique, giving relevance to the interrelationships among image, quality, satisfaction, and trust and among these variables and the tourists' behavior variables. Instruments are identified and exploratory research was undertaken among rural tourists of the main rural lodgings in two border regions of Spain and Portugal. The results confirm image as a direct antecedent of perceived quality, satisfaction, trust, and loyalty for rural tourism, too. The analysis also confirmed that quality has a positive influence on satisfaction and loyalty, and trust has a positive influence on loyalty. Image is shown as a key factor to rural lodging managers. This study may help rural tourism managers to develop and implement effective relationship marketing strategies.